The Operational Characteristics of Voice And Movement In The Actor's Performance In The Department of Art Education (Journal of the College of Basic Education, 2026)
Voice and movement are the primary physical tools an actor possesses, through which he can convey a literary text and transform it into a lively, vibrant action, based on a dramatic structure guided by the actor, conveying the character's feelings, emotions, and emotions through gestures, movements, and spoken language within the performance space. The research may consist of four chapters, the first of which includes a review of the research problem included in the following question: What are the operational characteristics of voice and movement in the actor in the performances of the Department of Art Education? The second chapter includes two topics, the first: the operation of voice in the actor, The second: The movement’s operation in the actor. As for the third chapter: It included a review of the research methodology starting from the research methodology and arriving at the sample analysis. As for the fourth chapter, it presented the research results in which the researcher used the (Holste) equation to extract the weighted mean and the percentage weight so that the results become facts that carry statistical significance that can be generalized. A number of conclusions emerged, and the research concluded with sources and appendices.